2012
DOI: 10.3724/sp.j.1006.2012.00541
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Observation of Anther Development of Photoperiod/Thermo-sensitive Male Sterile Line Huiyou50S in Brassica napus

Abstract: A photoperiod/thermo-sensitive male sterile line, named Huiyou50S, was developed from a spontaneous semi-sterile plant found in Brassica napus cultivar Huiyou50. The male sterility of Huiyou50S was controlled by recessive nuclear genes. Huiyou50S presents male sterile under high temperature and long photoperiod condition, and fertility under low temperature and short photoperiod. The cytological characters of pollen and the anther development of Huiyou50S at the different stages were compared with its near iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Sun et al reported that microspores of the line H50S begins abortion after being released from the tetrads, no vacuole could be found in the aborted microspores, and the nuclei of the aborted microspores collapse [35]. Ge et al stated that pollen abortion occurs at the uninucleate stage in Huiyou 50S [15]. In TGMS SP2S line, anther abortion occurs at the early stage of PMC, the tapetal cells are already highly vacuolated and enlarged at this stage, and uninucleate microspores are finally degraded [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sun et al reported that microspores of the line H50S begins abortion after being released from the tetrads, no vacuole could be found in the aborted microspores, and the nuclei of the aborted microspores collapse [35]. Ge et al stated that pollen abortion occurs at the uninucleate stage in Huiyou 50S [15]. In TGMS SP2S line, anther abortion occurs at the early stage of PMC, the tapetal cells are already highly vacuolated and enlarged at this stage, and uninucleate microspores are finally degraded [7].…”
Section: Discussionmentioning
confidence: 99%
“…The previously reported P/TGMS lines in B. napus could be classified into two types, namely, TGMS and PTGMS. The first type includes Xiangyou 91S and its derivative Xiangyou 402S [9,10], 373S [11,12], 104S [13], 160S [14], Huiyou 50S [15,16], SP2S [7,17], 100S [18], and TE5A [19]. The second type comprises H90S [20], N196S [21] and 501-8S [22,23].…”
Section: Introductionmentioning
confidence: 99%